2014
DOI: 10.1002/jssc.201400141
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous determination of ethyl carbamate and 4-(5-)methylimidazole in yellow rice wine and soy sauce by gas chromatography with mass spectrometry

Abstract: We developed a new method, based on alkaline diatomite solid-phase extraction followed by gas chromatography with mass spectrometry, for the simultaneous determination of the toxic contaminants ethyl carbamate (EC) and 4-(5-)methylimidazole (4-MEI) in yellow rice wine and soy sauce. The optimal extraction conditions were defined. With the application of alkaline diatomite solid-phase extraction, damage to the capillary column by organic acids was greatly reduced. With deuterated EC used as the internal standar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…To our knowledge, the difference in 4‐MeI contents in cola obtained from fast food restaurants and bottled and canned colas from markets has never been reported previously. Our data were in good agreement with the previously reported values of 4‐MeI (94 to 325 μg/L) in cola in Korean markets as determined by headspace‐solid phase microextraction‐GC‐mass spectrometry (HS‐SPME‐GC‐MS) (Wu and others ). It is also interesting to note that the ranges of 4‐MeI contents in colas were similar, regardless of the countries.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…To our knowledge, the difference in 4‐MeI contents in cola obtained from fast food restaurants and bottled and canned colas from markets has never been reported previously. Our data were in good agreement with the previously reported values of 4‐MeI (94 to 325 μg/L) in cola in Korean markets as determined by headspace‐solid phase microextraction‐GC‐mass spectrometry (HS‐SPME‐GC‐MS) (Wu and others ). It is also interesting to note that the ranges of 4‐MeI contents in colas were similar, regardless of the countries.…”
Section: Resultssupporting
confidence: 92%
“…Analytical methods of gas‐liquid chromatography (GC), reversed‐phase chromatography (HPLC), or capillary isotachophoresis have been introduced for the analysis of 2‐ and 4‐MeI. Gas chromatography–mass spectrometry (GC–MS), liquid chromatography–mass spectrometry (LC–MS), and LC‐tandem mass spectrometry (LC–MS/MS) are the most common techniques for the analysis of MeI in foods (Hengel and Shibamoto ; Schlee and others ; Wu and others ). Direct GC‐MS in selective ion monitoring (SIM) mode without derivatization is not sensitive enough for the quantification of 4‐MeI due to its low volatility and high polarity (Lim and Shin ).…”
Section: Introductionmentioning
confidence: 99%
“…SPE can significantly reduce matrix interferences; some authors have reported detection of EC at the nanograms per liter (parts per trillion) concentration when samples are analyzed with GC-MS (37). However, the lengthy extraction procedure for EC analysis by GC-MS has encouraged researchers to develop methods that reduce sample preparation times (144,149,208).…”
Section: Analytical Methods For Determination Of Ec Concentrations In...mentioning
confidence: 99%
“…PGRs are often added during the bean sprout cultivation process to accelerate growth or improve the quality and quantity of the products. However, PGRs such as gibberellin A3 (GA 3 ), 2,4-dichlorophenoxy acetic acid (2,4-D), 4-chlorophenoxyacetic acid (4-CPA), indole-2-acetic acid (IAA), indole-3-butyric acid (IBA), forchlorfenuron (FCF), thidiazuron (TDZ), 6-benzyl adenine (6-BA), paclobutrazol (PBZ), and 6-furfurylaminopurine (6-KT) are forbidden for use in bean sprout production [2,4,5]. Nevertheless, reports of illegal PGR addition, such as through the application of "AB powder" (A contains 6-BA, and B contains GA 3 ), appear frequently enough to cause concern [6].…”
Section: Introductionmentioning
confidence: 99%
“…Several methods have been developed for analyzing the presence of PGRs in food samples, including GC [10,11], HPLC [12][13][14][15][16][17][18], GC-MS [5,19,20], electrochemical sensing method [21], and HPLC-MS [22][23][24][25][26][27]. The GC, HPLC, and GC-MS methods are often utilized, but some of these methods showed the complexity of samples pre-treatment and the low sensitivity of the detection results.…”
Section: Introductionmentioning
confidence: 99%